Actividades extracurriculares - Balseca Pallasco, Flor María (2017)
In Ecuador the educational processes suggest new learning ways, which put in evidence the creativity of the teachers, as well as the active participation of the children; and with that a space for interaction with activities outside the classroom so in this context, the descriptive research is applied because it is focused on analyzing the incidence of extracurricular activities in academic performance by applying techniques and other instruments such as observation, surveys aimed to parents, students and teachers so there were situations which gave a direct guidance to generate conclusions and recommendations. Teachers express that the educational curriculum is too extensive and if it needed to be completed there would not have been enough time to develop other activities which reflect other ways of interaction with the students at the same time parents establish a priority to carry out extracurricular activities in the school, because they are new ways of recreation and collaborative work among their kids, so most of them because of their own occupations, share few activities in this specific field with their children. Finally, there is an evidence that students are interested in being part of these activities such as sports, meetings, walks, hikes, tours so they are fundamental to propose proposals of this type, in order to contribute in a effective way to the integral development of students, with the direct participation of teachers, authorities and parents of the High School "Toacaso".